The Tim Carmody affair : Australia's greatest judicial crisis - Ananian-Welsh, Rebecca; Appleby, Gabrielle; Lynch, Andrew, 1973-; EBSCOhost (Sydney, NSW : NewSouth Publishing, 2016)
"When Tim Carmody was appointed Chief Justice of Queensland by Premier Campbell Newman in 2014, he had been Chief Magistrate for only nine months. It proved to be the most controversial judicial appointment in Australia's history. Carmody's elevation plunged the Supreme Court and the legal profession into a bitter conflict with the government and with Carmody himself. How did he come to be appointed to such a significant position? What can we learn from this saga about the fragile relationships between politics and the courts? The Tim Carmody Affair places the full story of Carmody's damaging and divisive tenure in context, and identifies key reforms that could prevent this kind of controversy in the future."--Website.
Includes index.
Includes bibliographical references and index.
eBook access via Internet.
Description based on online resource; title from digital title page (viewed on October 24, 2016)
Keywords: Carmody, Tim; Queensland. -- Supreme Court -- Officials and employees -- Selection and appointment; Queensland. -- Supreme Court; Judges -- Selection and appointment -- Australia -- Queensland; Judges -- Selection and appointment -- Queensland; Judicial independence -- Australia -- Queensland; Judicial independence -- Queensland; Judicial process -- Political aspects -- Australia -- Queensland; Judicial process -- Political aspects -- Queensland; Justice, Administration of -- Political aspects -- Australia -- Queensland; Justice, Administration of -- Political aspects -- Queensland; Indépendance judiciaire -- Australie -- Queensland; Justice -- Administration -- Aspect politique -- Australie -- Queensland; Processus judiciaire -- Aspect politique -- Australie -- Queensland; Judges -- Selection and appointment; Judicial independence; Judicial process -- Political aspects; Justice, Administration of -- Political aspects; LAW / Civil Procedure; LAW / Legal Services; POLITICAL SCIENCE / Government / Judicial Branch; Queensland; Australian; Electronic books; Electronic books